FISH FAUNA OF KEDAR VALLEY, CHAMOLI-GARHWAL - Baloni, S P (Indian Journal of Fisheries, 2011)
No attempt seems to have been made so far to explore the fish fauna ofKedar Valley, inspite of the richness of water resources and zoogeographical significance.Kedar valley is in Chamoli-Garhwal and is situated in North latitude30°-47' and East longitude 79°^8'. The main river of this valley is Mandakiniwith a number of tributaries. River Mandakini originates at an altitude of 3583metres at the southeastern base of Kedarnath peak, north latitude 30°-47' andeast longitude 79°-8'. The fishes were poUected both from the river and itstributaries.